Evaluation of Protein S and Protein C Levels in B-Thalassemic Patients and Its Association with Blood Transfusion - Sahar Hakeem Kareem; Maysem M. Alwash (Iraqi Journal of Cancer and Medical Genetics, 2020)
Background: Thalassemia is a chronic hemolytic anemia due to a partial or complete deficiency in the synthesis of α-globin chains or β-globin chains that compose of the major adult hemoglobin (α 2β 2). Protein C is a vitamin K-dependent serine protease and naturally occurring anticoagulant that plays a role in the regulation of hemostasis by inactivating factors Va and VIIIa in the coagulation cascade.Protein S is a non-enzymatic cofactor for activated protein C–mediated inactivation of factor VIIIa and Va. In addition, protein S may have activated protein C–independent anticoagulant activity. Aim of study:To evaluate protein S&C levels in thalassemic patients &its relation to blood transfusion .Methods: the study included 80 subjects divided into two groups: Case group included 60 patients who were a known cases of transfusion dependent B-thalassemia and control group included 20 participants who were healthy and matched in age and gender with case group. Patients with other forms of hemolytic anemia like sickle thalassemia, who suffering from severe hepatic or cardiac dysfunction, those with other hemoglobinopathies, were excluded from the study. Plasma protein S and C Ag were calculatedin both patient groups and in control group by ELISA.Results: Plasma protein C was significantly lower in patients with splenectomy in comparison with patients without splenectomy.Protein C and S were significantly lower in patients with non-frequent than in patients with frequent blood transfusion. There was significant positive correlation between plasma protein C and protein S levels.Conclusion: Patients with thalassemia major have lower level of protein C and protein S than non-thalassemic patient.Frequency of blood transfusion can affect level of protein C & protein S. Splenoctomized patients have lower levels of protein C and S than non-splenoctomized.